2002
DOI: 10.1038/sj.sc.3101298
|View full text |Cite
|
Sign up to set email alerts
|

Primary prevention of deep venous thrombosis and pulmonary embolism in acute spinal cord injured patients

Abstract: Study design: Prospective clinical trial. Objectives: To evaluate the e cacy of a speci®c protocol for prevention of thrombo-embolic disease occurring during the acute stage of spinal cord lesions, based on the simultaneous use of pharmacological plus mechanical procedures. Setting: Regional Spinal Unit of Florence, Italy. Introduction: Deep venous thrombosis (DVT) is a dangerous pathology whose ®rst clinical sign can be represented by unexpected pulmonary embolism (PE). Its incidence in acute spinal cord inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
94
1
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 20 publications
1
94
1
9
Order By: Relevance
“…6,18,19 Similarly, studies conducted in neighboring India to asses the risk of DVT in patients undergoing hip and knee arthroplasties reported the incidence of DVT to be 6.1% (Bagaria et al 4 ) and 2.8% ( Jain et al 20 ), respectively, which is significantly lower than the incidence in the West. 8,9 In our study, DVT was found to be more common in patients who had complete SCI and were immobilized for a longer period of time than the patients having incomplete injury or no neurological deficit and who were mobilized earlier. A recent report of complications in a different cohort of 194 SCI earthquake survivors found that only 3 patients (2%) developed DVT, with one dieing of a pulmonary embolism.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…6,18,19 Similarly, studies conducted in neighboring India to asses the risk of DVT in patients undergoing hip and knee arthroplasties reported the incidence of DVT to be 6.1% (Bagaria et al 4 ) and 2.8% ( Jain et al 20 ), respectively, which is significantly lower than the incidence in the West. 8,9 In our study, DVT was found to be more common in patients who had complete SCI and were immobilized for a longer period of time than the patients having incomplete injury or no neurological deficit and who were mobilized earlier. A recent report of complications in a different cohort of 194 SCI earthquake survivors found that only 3 patients (2%) developed DVT, with one dieing of a pulmonary embolism.…”
Section: Discussionmentioning
confidence: 51%
“…7 The prevalence of DVT following acute SCI in Western populations ranges from 5.4 to 28% with thromboprophylaxis. [8][9][10] The earthquake that struck Pakistan on the 8th October 2005 was a devastating tragedy that left 73 000 dead and 126 000 injured. Owing to the absence of a national trauma registry, an accurate assessment of the total number of cases of SCI was difficult to determine, but the estimates range from 650 to 750.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 However, it is significantly higher than the PE risk in the general population (0.06% per year). 10 Patients with a complete injury AIS A had a slightly higher rate of PE.…”
Section: Discussionmentioning
confidence: 88%
“…3 In the acute phase of SCI (up to 90 days post injury) the incidence of PE has been reported as 4.5% with a mortality rate of 3.5%. 5 The introduction of prophylactic anticoagulation therapy in the first 3 months was associated with a reduction in mortality rates. 6 Anticoagulation is usually ceased after 3 months post injury, based on autopsy evidence of rare incidences of PE in this period.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced vasomotor tonus, venous return and muscle contraction combined with hypercoagulability, immobility and direct damage to the deep venous system all predispose patients with SCI in the acute phase to DVT 28 .…”
Section: Discussionmentioning
confidence: 99%